A Portrait of the Nineteenth-Century Nusantara Ulema Network in Haramain (Transmission of Shaykh Mahfudz At-Tarmasi's Tafsir-Hadith in Kifāyat Al-Mustafīd) - Ghozali, Abdul Malik (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2024)
AbstractThe existence of isnad, or the transmission of the chain of narrators, is inseparable from the emergence of the Prophetic traditions. However, it turns out that in its development, isnad has been used to maintain the authenticity of the material of the Prophetic traditions and the scientific tradition's authenticity. Scholarly isnads grew rapidly among Muslim scholars, especially in the Middle East, in transferring knowledge among their communities. Not surprisingly, scholarly transmission became a 'benchmark' among scholars. Besides that, scholarly transmission became a portrait of the network built among the Nusantara scholars who studied in the Middle East, not spared the influence of this scientific transmission. Among them are Shaykh Muhammad Mahfudz at-Tarmasi, a scholar who lived in the 19th century, has multi-talents from Termas village, Pacitan, East Java, has immortalized his scientific transmission in a work “Kifāyat al-Mustafīd Lima 'Alā min al-Asānīd”.This study aims to reveal the network of Nusantara scholars at the time of Shaykh Mahfudz at Haramaian and the implications of ideological transformation and scientific legality through scientific transmission. This research uses a content analysis method with a historical approach and Rijal al-had science. The results of this study prove that the scientific sanad illustrates the network of Ulama in his time and the transformation of ideas among them through access to scientific transmission in addition to scientific legitimacy.Keywords: Isnad; Knowledge; Mahfudz Tarmasi; Network Transmission. AbstrakKeberadaan Isnad atau transmisi mata rantai perawi tidak dapat dipisahkan dari kemunculan hadis-hadis Nabi. Namun ternyata, dalam perkembangannya, isnad tidak hanya digunakan dalam menjaga otentisitas materi hadis-hadis Nabi SAW, tapi sudah digunakan untuk menjaga otentisitas tradisi keilmuan yang telah terbangun. Isnad keilmuan tumbuh pesat di kalangan sarjana-sarjana muslim, khususnya di Timur Tengah dalam mentransfer keilmuan di antara komunitas mereka. Tidak heran, transmisi keilmuan menjadi suatu ‘benchmark’ di kalangan para ulama. Bukan hanya itu, transmisi keilmuan menjadi potret jaringan yang telah terbangun di kalangan para ulama Nusantara yang belajar di Timur Tengah, tidak luput dari pengaruh transmisi keilmuan ini. Di antaranya Syaikh Muhammad Mahfudz at-Tarmasi, seorang ulama yang hidup pada abad XIX, memiliki multi talenta asal desa Termas, Pacitan, Jawa Timur, telah mengabadikan transmisi keilmuan yang dimilikinya dalam sebuah karya “Kifāyat al-Mustafīd Lima ‘Alā min al-Asānīd”. Penelitian ini bertujuan mengungkap jejaring Ulama Nusantara pada masa Syaikh Mahfudz di Haramaian dan implikasi transformasi ideologi serta legalitas keilmuan melalui transmisi keilmuan. Penelitian ini menggunakan metode content analysis dengan pendekatan sejarah dan ilmu rijal al-hadis. Hasil penelitian ini membuktikan bahwa sanad keilmuan menggambarkan jejaring Ulama di masanya dan transformasi ide di antara mereka melalui akses transmisi keilmuan selain sebagai legitimasi keilmuan. Kata Kunci: Isnad; Jaringan; Knowledge; Mahfudz Tarmasi; Transmission.